Association Between Prenatal Smoking and Gestational Diabetes Mellitus. Issue 1 (January 2020) - Bar-Zeev, Yael; Haile, Zelalem T.; Chertok, Ilana Azulay
Abstract : OBJECTIVE: To evaluate whether there is an association between prenatal smoking and gestational diabetes mellitus (GDM). METHODS: We conducted a secondary data analysis using data from the Pregnancy Risk Assessment Monitoring System from 2009 to 2015. Outcome measures included self-reported GDM and change in smoking status during pregnancy (nonsmoker, quit smoking, reduced the amount smoked, smoked the same or more). Multivariable logistic regression analyses were performed to estimate the association between prenatal smoking and GDM status, adjusted for maternal age, race–ethnicity, prepregnancy body mass index (BMI) categories (underweight, normal [referent group], overweight, and obese), and gestational weight gain (inadequate, normal [referent group], and excessive), overall and stratified by prepregnancy BMI and gestational weight gain subgroups. RESULTS: A total of 222, 408 women were included; 5.3% (n=12, 897) had GDM. Most (48.1%) women had normal prepregnancy BMI, and 43.1% had excessive gestational weight gain. Mothers who continued to smoke the same or greater number of cigarettes or reduced the number of cigarettes smoked had higher odds of GDM (adjusted odds ratio [OR] 1.46, 95% CI 1.25–1.71 and OR 1.22, 95% CI 1.08–1.38, respectively). Smoking the same or more cigarettes was associated with higher odds of GDM in all subgroups of prepregnancy BMI or gestational weight gain. CONCLUSION: Prenatal smoking is associated with higher odds of GDM, after adjusting for known risk factors, and stratifying by prepregnancy BMI and gestational weight gain. Reducing smoking during pregnancy might reduce the risk of GDM and could be an additional reason for promoting smoking cessation among pregnant women. Abstract : Even after adjusting for known risk factors, prenatal smoking is associated with higher odds of developing gestational diabetes mellitus.